AKT-Independent Protection of Prostate Cancer Cells from Apoptosis Mediated through Complex Formation between the Androgen Receptor and FKHR - Li, Pengfei (American Society for Microbiology, 2003)
Recent studies suggested that the protection of cell apoptosis by AKT involves phosphorylation and inhibition of FKHR and related FOXO forkhead transcription factors and that androgens provide an AKT-independent cell survival signal in prostate cancer cells. Here, we report receptor-dependent repression of FKHR function by androgens in prostate cancer cells. Transcriptional analysis demonstrated that activation of the androgen receptor caused an inhibition of both wild-type FKHR and a mutant in which all three known AKT sites were mutated to alanines, showing that the repression is AKT independent. In vivo and in vitro coprecipitation studies demonstrated that the repression is mediated through protein-protein interaction between FKHR and the androgen receptor. Mapping analysis localized the interacting domains to the carboxyl terminus between amino acids 350 and 655 of FKHR and to the amino-terminal A/B region and the ligand binding domain of the receptor. Further analysis demonstrated that the activated androgen receptor blocked FKHR's DNA binding activity and impaired its ability to induce Fas ligand expression and prostate cancer cell apoptosis and cell cycle arrest. These studies identify a new mechanism for androgen-mediated prostate cancer cell survival that appears to be independent of the activity of the receptor on androgen response element-mediated transcription and establish FKHR and related FOXO forkhead proteins as important nuclear targets for both AKT-dependent and -independent survival signals in prostate cancer cells.